Long-term self-reported attendance in exercise training or lung choir and status of quality of life following initial pulmonary rehabilitation for COPD - Kaasgaard, Mette; Bodtger, Uffe; Skou, Søren T.; Clift, Stephen; Hilberg, Ole; Rasmussen, Daniel Bech; Løkke, Anders (Frontiers in Rehabilitation Sciences, 2024)
BackgroundBoth adherence rates to pulmonary rehabilitation (PR) programmes and long-term attendance in exercise training after PR remain a challenge. In our previous randomised controlled trial (RCT), effects were positively associated with a dose-response pattern, regardless of whether PR contained conventional physical exercise training (PExT) or Singing for Lung Health (SLH) as a training modality within a 10 weeks’ PR programme for chronic obstructive pulmonary disease (COPD). However, long-term status of this RCT cohort remains unknown. In this study, we investigated whether current status (=attendance in supervised exercise training or a lung choir and scoring in quality of life (QoL)) was related to initial PR completion, randomisation, or adherence.MethodsWe collected data via telephone, using a researcher-developed questionnaire on current self-reported attendance in supervised exercise training or a lung choir and on perceived benefits of the initial RCT intervention. Additionally, we used COPD-validated questionnaires (primarily: QoL (measure: St George's Respiratory Questionnaire; SGRQ).ResultsIn 2023 (i.e., mean/median 4.7 years after initial PR), surviving participants were contacted (n = 196; 73% of 270), and 160 (82% of 196) were included. Out of the included participants, 30 (19%) had not completed initial PR. Compared to the initial PR-completers, non-completers reported less current attendance in exercise training or lung choir (24% vs. 46%, p = 0.03) but SGRQ scores were comparable. Yet, those who attended exercise training or lung choir at present (n = 66/160; 41% out of 160) reported better QoL score than those with no current attendance (SGRQ; Attending: 39.9 ± 15.4; Not attending: 43.1 ± 16.7; p = 0.02). Neither having had SLH instead of PExT, nor adherence level during initial PR, was related to current attendance or to QoL scores.ConclusionThis study indicates that long-term self-reported attendance and current QoL scores are positively related to initial completion of a PR programme. Surprisingly, neither initial PR content (PExT or SLH) nor initial PR adherence was related to long-term outcomes. We suggest that future PR programmes include special attention to those who do not complete PR to support long-term attendance and QoL status.